Arilsulfonilação tri componente de diidrofurano e ésteres vinílicos via catálise dual níquel/fotorredox - Pugnal, Lucas Valentin Bosi Loss (2022)
The pursuit of synthetic protocols aligned to sustainability goals, increasingly necessary in the global context in which we operate, caused a great effort by synthetic chemists to develop photocatalytic methodologies applied to different transformations. Moreover, the development of novel cross-coupling protocols has remained in the academia focus since seminal reports in this field, which rendered the 2010 chemistry Nobel prize for Heck, Negishi and Suzuki. In the past few years, many research groups worked in order to combine both methods, which led to development of systems we now call metallaphotoredox. Such combination is highly interesting once it can merge both catalytical cycles in a synergistic way, mitigating their main individual disadvantages as well as paving the way for new reactivities, unreachable by both methodologies alone. Among its numerous applications, intermolecular alkene difunctionalization has been widely explored in recent years. In this context, in this work the development of a new strategy for tricomponent arylsulfonylation of 2,3-dihydrofuran and vinyl esters via dual Ni/photoredox catalysis took place. Employment of the developed protocol led to 35 examples of arylsulfonylated tetrahydrofuran scaffolds with yields up to 95% and 3 examples of arylsulfonylated vinyl esters.